Prognosis and Treatment of Headaches - J Gordon Millichap (Pediatric Neurology Briefs, 1995)
The prognosis and methods of coping with headaches were studied by telephone interview in 98 children followed for 10 years after diagnosis at the Department of Pediatrics, Dalhousie University and Children’s Hospital, Halifax, Canada.